Implantable cardiac devices technology - Korpas, David (Springer US, 2013)
Development in a majority of medicine branches today is  based on technological advancement. This is the case in cardiology, where medical devices designed to correct heart rhythm - pacemakers, cardioverters-defibrillators and biventricular systems - are implanted in order to help a sick heart. Medical pacing devices today are only developed and produced globally by a several producers who make different technical solutions, algorithms, system parameters etc. The book Implantable Cardiac Devices Technology is targeted at biomedical, clinical engineers, technicians in practice, students of biomedical disciplines,  and all medical staff  who are required to understand the basics of pacing technology. The book is comprised of  fourteen chapters that are further subdivided according to specific topics. Chapters dealing with basic heart anatomy, physiology and arythmology are included for the sake of comprehensiveness. Chapters avoid the description of special functions, but  cover general procedures and parameters common for the systems of all producers. The book is intended to serve as a monothematic textbook.  In order to make the text comprehensible and well arranged for a reader, references to professional literature are only provided once in a respective chapter.